1998
DOI: 10.1203/00006450-199810000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Lower Incidence of Necrotizing Enterocolitis in Infants Fed a Preterm Formula with Egg Phospholipids

Abstract: Necrotizing enterocolitis (NEC) causes approximately 4000 deaths/y and significant morbidity among U.S.-born preterm infants alone. Various combinations of inadequate tissue oxygenation, bacterial overgrowth, and enteral feeding with immaturity may cause the initial damage to intestinal mucosa that culminates in necrosis. Presently, there is not a way to predict the onset of the disease or to prevent its occurrence. As part of risk-benefit assessment, we compared disease in hospitalized preterm infants fed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 69 publications
2
82
0
2
Order By: Relevance
“…Many circulating components are in fact regulation. There is evidence pointing to the possibility that de®cits of AA and DHA may contribute to the complications of prematurity (Crawford et al, 1998) and Carlson et al (1998) has recently described a signi®cant preventive effect against necrotizing enterocolitis by supplementing preterm infants with AA and DHA. Most studies on diet and lipids have been done on storage lipids, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Many circulating components are in fact regulation. There is evidence pointing to the possibility that de®cits of AA and DHA may contribute to the complications of prematurity (Crawford et al, 1998) and Carlson et al (1998) has recently described a signi®cant preventive effect against necrotizing enterocolitis by supplementing preterm infants with AA and DHA. Most studies on diet and lipids have been done on storage lipids, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies reported other relevant neonatal outcomes, such as number of days of ventilation, or the use or duration of supplementation oxygen, 13,20,22,27,28 patent ductus arteriosus, 12,20,23,[30][31][32] cholestasis, 31,32 or number of days of hospital admission. 8,11,13,18,31,32 Effect Estimates for Dichotomous Neonatal Outcomes…”
Section: Characteristics Of Exposure and Outcomesmentioning
confidence: 99%
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Furthermore, TLR4 activation leads to induction of inflammatory molecules such as TNFα [102] and nitric oxide (NO) [103]; both of these molecules have been shown to be involved in NEC pathogenesis [15,81,104] and have been shown to be pro-apoptotic for enterocytes [81,105]. It is notable that other GPCRs that are closely related to PAFR may impart either pro or anti-apoptotic signals on enterocytes as discussed above [41, 99,100] signaling in other cell types that can actively promote inflammation such as PMN [106] and lymphocytes [108]. These findings suggest that we are only beginning to skim the surface of the intricate mechanisms of GPCR-mediated cell death and survival and that other GPCRs may play significant roles in NEC.…”
Section: Pro-apoptotic Signaling In Necmentioning
confidence: 99%
“…Several years ago, a clinical study that was geared towards evaluating the efficacy of polyunsaturated fatty acid (PUFA) supplementation to premature neonatal formula to improve long term neurodevelopmental outcomes has found, as an incidental finding, that PUFA supplementation reduced the incidence of NEC [108]. In order to verify these findings and to further understand the mechanisms that may be involved in this unexpected beneficial effect of PUFA, in two subsequent studies we have shown that PUFA supplementation to formula dramatically reduced the incidence of NEC in rodent models of NEC [109,110].…”
Section: Nutrition Pafr Signaling Apoptosis and Necmentioning
confidence: 99%